2014
DOI: 10.2174/0929867321666131228204246
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ion – The Key Player in Cerebral Ischemia

Abstract: Role of calcium ion (Ca2+) in the functioning of neurons from their naïve state to mature state is of vital importance. It controls functions such as neuronal functioning, neuronal ATP production, central nervous system migration and many others. Failure in Ca2+ homeostasis mechanisms and the resulting cellular Ca2+ ion load initiates a cascade of reactions involving various cytosolic enzymes and proteins. This total mechanism leads to the neuronal death. The ability of neurons to resist such death mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 0 publications
1
56
1
1
Order By: Relevance
“…Calcium ion accumulation has been suggested to be a key regulator of cell survival, but these ions can also induce apoptosis in neuronal death (Kumar et al 2014). Mitochondria are essential for the production of ATP, through oxidative phosphorylation, the regulation of intracellular Ca 2+ homeostasis, and they are the main generators of ROS Espino et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ion accumulation has been suggested to be a key regulator of cell survival, but these ions can also induce apoptosis in neuronal death (Kumar et al 2014). Mitochondria are essential for the production of ATP, through oxidative phosphorylation, the regulation of intracellular Ca 2+ homeostasis, and they are the main generators of ROS Espino et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cation channels play a significant role in modulating intracellular Ca 2+ concentrations in all cells, including neurons, because Ca 2+ passes the cell membranes to enter the cytosol by way of these channels (Nazıroğlu, 2012;Kumar et al, 2014).…”
Section: +mentioning
confidence: 99%
“…Mitochondrial injury induces a decrease in the activities of mitochondrial complexes and ATP synthesis and it induces a further increase in ROS production in the mitochondria. Thus, mitochondrial depolarization is triggered and fueled by Ca 2+ entry from the extracellular space via TRP and NMDA channels when triggered by neuronal activity (Nazıroğlu, 2009;Kumar et al, 2014;Tök et al, 2014). Recently we reported that Ca 2+ entry is involved in epilepsy and oxidative stress-induced hippocampal and DRG death through activation of TRPV1 channels, and negative modulation of this channel activity by CPZ pretreatment may account for the neuroprotective activity against oxidative stress (Ghazizadeh and Nazıroğlu, 2014).…”
Section: Melatonin and Trp Channelsmentioning
confidence: 99%
“…Intracellular free Ca 2+ concentration ([Ca 2+ ] c ) homeostasis is involved in many functions such as cellular viability, apoptosis, physiological signal transduction, and extensive production of ROS [6]. The [Ca 2+ ] c is controlled by a number of membrane cation channels.…”
Section: Introductionmentioning
confidence: 99%